(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This paper examines the evolution of Indian women's English poetry from its marginal status to its current position in the global literary mainstream. By analyzing the works of key poets from the post-independence era to the present day, this study traces the thematic and stylistic developments that have characterized this journey. The research highlights how these poets have addressed issues of gender, identity, and cultural hybridity, contributing to both Indian and global feminist discourses. The paper also explores the challenges faced by these poets and the critical reception of their work in India and abroad, concluding with a discussion of future directions for Indian women's English poetry in the global context.